Soluções positivas de um sistema elíptico semilinear nos casos crítico e supercrítico - Reis, Fernando Pereira Paulucio (2011)
In this work we study the existence of multiple positive solutions for a system of elliptic equations involving critical Sobolev exponent in a bounded domain in RN. These results were demonstrated by Pigong Han. The sub-supersolution method allows to obtain a minimal solution when a parameter " > 0 is small enough. In the critical case, by using the variational method, we may prove the existence of a second positive solution. In the supercritical case, by using the Pohozaev identity, we obtain that the existence of solutions is related to the existence of nonnegative solutions for two linear elliptic problems